Mapping of Signaling Pathways Linked to sIgAD Reveals Impaired IL-21 Driven STAT3 B-Cell Activation - Lemarquis, Andri L.; Theodors, Fannar; Einarsdottir, Helga K.; Ludviksson, Bjorn R. (Frontiers in Immunology, 2019)
Abstract Objectives It has recently been shown that individuals with selective IgA deficiency (sIgAD) have defective B cell responses both to T cell dependent and independent mimicking stimulations. The complex intracellular signalling pathways from different stimuli leading to IgA isotype switching have not been fully elucidated. Thus, the main objective of this study was to delineate these pathways and their potential role in the immunopathology linked to sIgAD. Materials and Methods PBMCs from 10 individuals with sIgAD and 10 healthy controls (HC) were activated in vitro via either a T cell dependent or independent mimicking stimulation. Intracellular phosphorylation of pSTAT3, pSTAT5, pSTAT6 and as pERK1/2 was evaluated in T and B cells using phosphoflow cytometry. Results By evaluating T cell dependent cytokine driven pathways linked to IgA isotype induction we identified a defect involving an IL-21 driven STAT3 activation isolated to B cells in sIgAD individuals. However, all other signalling pathways studied were found to be normal compared to HC. In T cell dependent cytokine driven stimulations linked to IgA isotype induction the following patterns emerged: (i) IL-10 led to significant STAT3 activation in both T- and B cells; (ii) IL-4 stimulation was predominantly confined to STAT6 activation in both T- and B cells, with some effects on STAT3 activation in T-cells; (iii) as expected, of tested stimuli, IL-2 alone activated STAT5 and some STAT3 activation though in both cases only in T-cells; (iv) IL-21 induced significant activation of STAT3 in both T- and B cells, with some effects on STAT5 activation in T-cells; and finally (v) synergistic effects were noted of IL-4+IL-10 on STAT5 activation in T-cells, and possibly STAT6 in both T- and B cells. On the other hand, CPG induced T cell independent activation was confined to ERK1/2 activation in B cells. Conclusion Our results indicate a diminished STAT3 phosphorylation following IL-21 stimulation solely in B cells from sIgAD individuals. This can represent aberrant germinal center reactions or developmental halt. Thus, our work provides further insight into the unraveling of the previously hypothesized role of IL-21 to reconstitute immunoglobulin production in primary antibody deficiencies.